2007
DOI: 10.1177/1087057107309036
|View full text |Cite
|
Sign up to set email alerts
|

Robust Hit Identification by Quality Assurance and Multivariate Data Analysis of a High-Content, Cell-Based Assay

Abstract: Recent technological advances in high-content screening instrumentation have increased its ease of use and throughput, expanding the application of high-content screening to the early stages of drug discovery. However, high-content screens produce complex data sets, presenting a challenge for both extraction and interpretation of meaningful information. This shifts the high-content screening process bottleneck from the experimental to the analytical stage. In this article, the authors discuss different approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 15 publications
1
32
0
Order By: Relevance
“…For reducing the number of parameters describing the cell images, supervised methods have been used and reviewed in the literature. 10,25,26 Such methods select parameters based on whether a given set of control samples can be classified correctly. This limits the use of these methods to cases for which control samples are available and when one seeks to identify compounds exactly leading to the same phenotype as displayed in the positive controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For reducing the number of parameters describing the cell images, supervised methods have been used and reviewed in the literature. 10,25,26 Such methods select parameters based on whether a given set of control samples can be classified correctly. This limits the use of these methods to cases for which control samples are available and when one seeks to identify compounds exactly leading to the same phenotype as displayed in the positive controls.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Nevertheless, there are many examples in the literature demonstrating the benefits of a multiparametric analysis of HCS data. For example, the validation rate of hits determined using a support vector machine (SVM) was higher than using a standard analysis, 10 or a compound's target could be predicted based on a phenotypic profile. 11 It was also shown that by integrating phenotypic profiles obtained by HCS with chemical similarity, mode of action (MoA) could be inferred.…”
mentioning
confidence: 99%
“…Alternatively, supervised machine learning techniques such as linear discriminant analysis, support vector machines, or neural networks could be employed. 7 Nevertheless, the choice of a suitable training set for these methods can be challenging since overfitting of the models toward the phenotypes that are part of the training set can occur.…”
Section: Comparison Of Similarity Measure Performancementioning
confidence: 99%
“…It has been shown that hit identification with multiple HCS readouts can lead to lower rates of false positives and therefore reduced attrition rates at the hit verification stage. 6,7 Image-based readouts are composed of morphological, geometric, intensity, and texture-based features that can be combined to create a mathematical vector. This feature vector represents the treatment-induced phenotypic effect and provides a biologically relevant descriptor of a compound, which can be regarded as a signature or fingerprint and is thus named HCS fingerprint here.…”
Section: Introductionmentioning
confidence: 99%
“…HCS is the cell-based quantification of several processes simultaneously, which provides a more detailed representation of the cellular response to various perturbations compared to HTS. HCS has many advantages over HTS 18,19 , but conducting a high-throughput (HT)-high-content (HC) screen in neuronal models is problematic due to high cost, environmental variation and human error. In order to detect cellular responses on a 'phenomics' scale using HC imaging one has to reduce variation and error, while increasing sensitivity and reproducibility.…”
mentioning
confidence: 99%